Peran pengungkapan lingkungan dan sosial terhadap return saham - Sumani, Sumani; Limawan , Tamara Letitia (Universitas Kristen Maranatha, 2024)
The world community has begun to realize the importance of sustainability amidst the many adverse conditions. In Indonesia, all public companies and financial institutions are required to publish sustainability reports which include information regarding their environmental and social responsibilities. This study aimed to elucidate the impact of corporate environmental and social disclosures on stock returns, moderated by profitability. By selecting the moderating variable and using the LQ-45 index for a certain period, the researchers hope that the results will create novelty from previous research and give rise to new information. The Sustainability Report (SR) is evaluated by the quantity of sustainable items reported in the Sustainability Report Disclosure Index (SRDI) in accordance with the Global Reporting Initiative (GRI) Standards, relative to the number of sustainable goods that ought to be disclosed. For environmental, social, and governance variables, compare the quantity of declared environmental, social, and governance elements in the SRDI to the quantity that ought to be disclosed. This study employs the Moderated Regression Analysis (MRA) technique utilising SPSS software. This study's population comprised 45 companies from the LQ-45 Index, incorporated in the IDXESGL index utilising the GRI Index, from February to July 2024, which issued sustainability and annual reports for 2021-2022, marking the inception of the IDXESGL Index. Thirty-five companies met the criteria. This study uses a data processing program, the SPSS version 25. This study employs descriptive statistical tests, coefficient of determination tests, and hypothesis testing for data analysis. The findings of this study demonstrate no impact of environmental and social transparency on stock returns. Profitability as a moderating element does not enhance the impact of social transparency on stock returns. Nonetheless, profitability can enhance the impact of environmental disclosure on stock returns.